2017
DOI: 10.4067/s0717-75182017000300234
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulación de hierro: Otra estrategia para la prevención o tratamiento de la anemia por deficiencia de hierro

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 42 publications
1
6
1
7
Order By: Relevance
“…On the other hand, Durán et al (2017) reported a release time of three hours of the sensitive components, such as minerals and vitamins, encapsulated with SA in media with a pH above 6.5, which corresponds to the results found in this study. Based on the results found, it would be advisable to incorporate the iron microcapsules obtained by electrostatic coacervation, in foods with acidic pH to ensure their integrity and preservation of Fe for a longer time.…”
Section: Fe Release Profile Of Sa/fs Microcapsulessupporting
confidence: 90%
See 3 more Smart Citations
“…On the other hand, Durán et al (2017) reported a release time of three hours of the sensitive components, such as minerals and vitamins, encapsulated with SA in media with a pH above 6.5, which corresponds to the results found in this study. Based on the results found, it would be advisable to incorporate the iron microcapsules obtained by electrostatic coacervation, in foods with acidic pH to ensure their integrity and preservation of Fe for a longer time.…”
Section: Fe Release Profile Of Sa/fs Microcapsulessupporting
confidence: 90%
“…Valenzuela et al (2014), reported capsules from 830 µm to 1.57 mm, using Dehydrated Bovine Erythrocytes (EBDA) as a source of iron using classical coacervation. Durán et al (2017) reported that iron encapsulation using spray drying generated particle sizes between 200 and 600 µm, smaller than those found in the present work.…”
Section: Estabilidad Térmica De La Microcápsulacontrasting
confidence: 85%
See 2 more Smart Citations
“…El sulfato ferroso y el fumarato ferroso son los compuestos en los cuales el hierro se encuentra más biodisponible. Si bien estas sales son solubles en agua o en ácido diluido, a menudo reaccionan con otros componentes de los alimentos, causando sabores desagradables, cambios de color u oxidación de lípidos (Durán et al, 2017). Por esta razón, para la fortificación de alimentos, se encuentran disponibles en el mercado el sulfato y fumarato ferroso encapsulados.…”
Section: Absorción De Hierro Y Fortificación De Alimentosunclassified